Anglers' views on stock conservation: Sea bass angling in Ireland - Gianluca Grilli; John A. Curtis; Stephen Hynes; Paul O'Reilly (The Economic and Social Research Institute (ESRI), 2017)
Bottom-up approaches to natural resource management are considered to be more effective for conservation than traditional top-down approaches because the policy-making process is legitimized by stakeholders. In particular, when decisions are shared with direct users of the resource, compliance with the law may be achieved more easily and potential sources of conflict averted. However, empirical evidence on this topic is still limited. In this paper, we investigate how recreational anglers perceive stricter legislation for sea bass fishing, using Ireland as a case study. The new legislation aims to limit harvest rates to restore a viable bass population following years of declining stocks. Data were collected by means of an angler survey and analysed with a seemingly unrelated ordered probit model. Results suggest that most respondents are willing to trade harvested fish for a healthier and long-term sustainable bass population, suggesting strong compliance with this new law.
Keywords: 330